Medical communication, internalized “good mother” norms, and feminist self-identification as predictors of maternal burnout - Milman, Daisy; Sternadori, Miglena (Frontiers in Communication, 2024)
Introduction A rarely studied source of psychological discomfort for mothers is the communication received from medical professionals in the context of pregnancy, childbirth, the postpartum period, and pediatric care. To address this gap, we examined mothers’ recollections of medical communications that influenced their perceived stress levels in the context of good-mother normativity. We also explored how recollections of feedback on mothering in medical settings were associated with internalization of good-mother expectations, maternal burnout, length of motherhood, and feminist self-identification. Methods We collected the data through an online survey administered by a company that pre-establishes business relationships with potential survey takers. The survey-takers were 254 self-identified mothers, who answered open-ended questions about their recollections of medical communications related to good-motherhood norms. The participants also completed measures of maternal burnout, internalized good mother expectations, and feminist self-identification, and answered demographic questions such as age, education, number of children, and how long they had been mothers. Results Participants who recalled discomfort-inducing medical communications that directly or indirectly referenced motherhood norms reported higher levels of internalized good-mother expectations and maternal burnout. A process model showed that the frequency of recalled medical communications, length of motherhood, and feminist self-identification moderated the relationship between the degree of internalization of good-mother expectations and maternal burnout. A significant association emerged between feminist self-identification and the recalled frequency of interactions with medical professionals that increased mothers’ perceived stress stemming from good-mother normativity. Discussion The findings of this study contribute to self-discrepancy theory as it relates to the social construction of mothers’ identities by focusing on whether and how often medical professionals reinforce or challenge good-mother social expectations. Another theoretical contribution of this study is that values and beliefs, such as feminist self-identification, can affect the recall of communications about social norms and are significantly associated with levels of internalized expectations and resulting burnout. In terms of practical implications, our findings suggest that medical professionals should be mindful of how they assess patients through the lens of the good-mother norms and also consider addressing the discomfort stemming from such normativity by asking mothers about their perceptions of social expectations and addressing unrealistic beliefs that aggravate mothers’ sense of self-discrepancy.